The relationship between trust, monitoring mechanisms, communication, and work performance of academicians in Malaysian Private Universities - Tan, Luen Peng (2013)
Undoubtedly, today private universities are mounting their efforts to become competitive in international arena. Private universities are currently embarking drastic restructuring mechanisms to sustain their competitiveness in the industry. Thus, the works of the academicians have become more challenging than before and they are expected to be productive at the same time. Element such as trust is essential to the creation and maintenance of conducive and enjoyable working environment in private universities. Although the relationship between trust and work performance have often been examined in other parts of the world, there is little empirical evidence to support this standpoint from the Malaysian perspective. The objectives of this study is to examine the relationship between trust and work performance and the moderating effect of monitoring mechanisms and communication on the relationship between trust and work performance in Malaysian private universities.The conceptual framework used in this study was tested using empirical data from 300 full-time academicians from Malaysian private universities. Stratified proportionate random sampling technique was used in this study and data from the survey were analyzed using Hierarchical Regression analysis. This study chooses hypothesis-testing or the explanatory design as the research design. Furthermore, this study is deductive in nature; consequently, a quantitative methodology by using survey (mail questionnaire) was employed. In addition, this study adopted the dimension of trust suggested by Mayer and Davis (1999); cognitive-based trust and affective-based trust dimensions questionnaire suggested by McAllister (1995) to measure trust. Moreover, this study adopted the dimension of communication suggested by Johlke and Duhan (2000) to measure communication and monitoring mechanisms suggested by McAllister (1995) to measure monitoring mechanisms. This study adopted the dimension of work performance suggested by Kathiraveloo, Uli, Samah, Othman, Ali, Hassan and Shaffri (2010) to measure work performance. Six institutional characteristics were employed in this study: gender, age, ethnic, tenure, qualification, and position. Results of the analysis indicated that there was a moderate level of trust, monitoring mechanisms and communication perceived by the academicians. However, the academicians in Malaysian private universities perceived that there was a high level of work performance and generally agreed that they were able to accomplish their work tasks to attain the goals set forth by the universities.Moreover, results of the analysis indicated that there is a positive relationship between trust and work performance. In addition, this study has also identified the relationship between individual trust dimensions namely trustworthiness, cognitive-based trust and affective-based trust and work performance. All the three dimensions of trust were found to have positive relationship with work performance. This implies that generally, trustworthiness, cognitive-based trust and affective-based trust are significant predictors of academicians’ work performance. The results of this study revealed that there was a moderating effect of monitoring mechanisms on the relationship between trust and work performance. 8.7% increase in variance in the work performance was due to the moderating effect of monitoring mechanisms. This finding provides empirical support for the moderating effect of monitoring mechanisms on the relationship between trust and work performance. As such, the empirical evidence has contributed to the body of knowledge of trust specifically as there is still lack of empirical research evidences by examining the moderating effect of monitoring mechanisms on trust and work performance. This results of this study also revealed that there was a moderating effect of communication on the relationship between trust and work performance. 6.8% increase in variance in the work performance was due to the moderating effect of communication. The finding of this study is pivotal in extending the notion of communication as a moderator on trust by incorporating multidimensional measurement of communication to holistically capture the essence of communication, especially its moderating role on trust and work performance. An important management implication of this study is that it facilitates the top level management by providing empirical information, which supports the vitality of trust cultivation and development and its positive influence on the academicians’ work performance, particularly in the Malaysian private universities. On the other hand, it is essential for the top management of the university to concentrate on the necessity of imposing monitoring mechanisms on the academicians. Moreover, the heads of department should encourage frequent communication with the academicians to understand the work problems that exist and their needs as well as expectations of the academicians toward the heads of department and vice versa. In addition, the findings from this study would fill the vacuum in the body of knowledge concerning trust, monitoring mechanisms, communication and work performance.